Analisis Empiris Terhadap Perlindungan Hak Pekerja Yang Terkena Pemutusan Hubungan Kerja Yang Dilakukan Oleh Pt Sariwiguna Bina Sentosa (Sbs) Dibangka Bangka Belitung - Muhammad Raihan Rawadi (Jurnal Hukum Lex Generalis, 2025)
Termination of Employment (PHK) in the tin mining sector of Bangka Belitung is a crucial labor issue. This study analyzes the protection of workers’ rights affected by layoffs at PT Sariwiguna Bina Sentosa (SBS) using an empirical juridical approach through interviews, document studies, and field observations. The findings show obstacles such as limited access to legal information, weak bargaining power, complicated claims procedures, and minimal legal assistance and government oversight. The study recommends improving workers’ legal literacy, strengthening the role of labor unions, simplifying claim mechanisms, and optimizing supervisory systems to ensure effective and sustainable worker protection.